Control of Ca2+ signals by astrocyte nanoscale morphology at tripartite synapses. Issue 12 (13th September 2022) - Denizot, Audrey; Arizono, Misa; Nägerl, U. Valentin; Berry, Hugues; De Schutter, Erik
Abstract: Much of the Ca 2+ activity in astrocytes is spatially restricted to microdomains and occurs in fine processes that form a complex anatomical meshwork, the so‐called spongiform domain. A growing body of literature indicates that those astrocytic Ca 2+ signals can influence the activity of neuronal synapses and thus tune the flow of information through neuronal circuits. Because of technical difficulties in accessing the small spatial scale involved, the role of astrocyte morphology on Ca 2+ microdomain activity remains poorly understood. Here, we use computational tools and idealized 3D geometries of fine processes based on recent super‐resolution microscopy data to investigate the mechanistic link between astrocytic nanoscale morphology and local Ca 2+ activity. Simulations demonstrate that the nano‐morphology of astrocytic processes powerfully shapes the spatio‐temporal properties of Ca 2+ signals and promotes local Ca 2+ activity. The model predicts that this effect is attenuated upon astrocytic swelling, hallmark of brain diseases, which we confirm experimentally in hypo‐osmotic conditions. Upon repeated neurotransmitter release events, the model predicts that swelling hinders astrocytic signal propagation. Overall, this study highlights the influence of the complex morphology of astrocytes at the nanoscale and its remodeling in pathological conditions on neuron‐astrocyte communication at so‐called tripartite synapses, where astrocytic processes come into close contact with pre‐ and postsynaptic structures. Main Points: Astrocyte nano‐morphology favors the compartmentalization of biochemical signals. This compartmentalization promotes local Ca 2+ activity and signal propagation robustness. In contrast, its pathological remodeling upon swelling attenuates Ca 2+ activity.